Three new species of Alepia Enderlein (Diptera, Psychodidae, Psychodinae) from the Brazilian semi-arid region - Bravo, Freddy (Zootaxa, 2008)
Three new species of Alepia Enderlein from the semi-arid region of Bahia State, northeastern Brazil are described: A. montana sp. nov., A. arenivaga sp. nov., and A. fervida sp. nov. Currently, eight species of Psychodidae are known from the semi-arid area (including the three species here described)—a region characterized by a long dry season (6–11 months) and low precipitation levels (300–1000 mm/year). A list of the eight species of Psychodidae from the Brazilian semi-arid region is provided.